Aspek Hukum Terhadap Perlindungan Pasien dalam Pelayanan Kesehatan Tradisional Menurut Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Jaury Douglas Pardomuan; Handoyo Prasetyo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Traditional medicine in Indonesia faces significant challenges regarding patient protection and clear regulation in the context of consumer protection. Unlike modern medicine that follows a structured European model, traditional medicine often lacks consistent definition and clear regulatory mechanisms. Law Number 17 of 2023 concerning Health seeks to accommodate the diversity of healthcare systems in Indonesia, yet there are still shortcomings in the responsibility of health organizations for the standardization and supervision of traditional medicine. This research analyzes how patient protection in traditional healthcare services is viewed from a consumer protection perspective and examines the implementation of Law Number 17 of 2023. Findings indicate the need for further steps to develop robust mechanisms in standardization, address deficiencies in health organizations responsible, and balance communal interests with individual needs in traditional medicine. Thus, these efforts are expected to enhance patient protection and improve the safety and effectiveness of traditional medicine in Indonesia.